CBOOK XCESS USAGE ON THE PROCESS OF TEACHING AND LEARNING OF CULINARY ARTS COURSE FOR SPECIAL NEEDS STUDENTS OF LEARNING DISABILITY (Proceedings of International Conference on Special Education, 2019)
Culinary Arts courses based on TVET that are the current choice of students to continue their studies at the secondary school level. Thus, special needs students are also not left behind to continue their studies in this area. The purpose of study is to examine the effectiveness of CBOOK XCESS as a teaching aids during cooking practical classes. This is because of the scarcity of teaching aids in Culinary Arts courses for special needs students in which causes them to have difficulty in remembering and understanding the cooking ingredients, cooking utensils, and the procedure during practical process. The objectives of this study are to look at the effectiveness of CBOOK XCESS as a teaching aids for cooking class session process; Enhancing special needs student’s assimilation during the cooking practical session: and Assist in stabilizing emotions of special needs students during cooking practical classes. CBOOK XCESS teaching aids is built from analytical framework, teaching aids design, teaching aids development, teaching aids implementation, and effectiveness evaluation have been used as a design for the development of teaching aid. The participants were eight special needs students with learning disability from SMPKV Merbok, Malaysia. The findings of the study are that the cooking practical session becomes more conducive, the students are more calm and able to continue successfully their cooking practical with the help of the teacher. Therefore, this study will contribute and become useful in the special education world based on TVET.